The Impact of Effective Microorganisms (EM) on Egg Quality and Laying Performance of Chickens - Alem Tadesse Atsbeha; Teweldemedhn Gebretinsae Hailu (International Journal of Food Science)
Chickens kept under modern production system are very small and contribute less than 2% of eggs and meat production in Ethiopia. In some parts of the country, effective microorganism (EM) has been used as a means of improving egg and meat production. However, there is information gap on the use and effect of EM on egg quality and laying performance of chickens in the local context. This study was conducted in Aksum University’s poultry farm located at the main campus in Axum, to evaluate egg laying performance and quality of eggs in layer chickens treated with effective microorganisms in feed and water. In this experiment, 180 pullets of ISA Brown chickens with uniform age and weight were used and managed in a cage system. Chickens were subjected to 4 treatments with 3 replications, and each replication consisted of 15 chickens. Data collection was started at the first egg lay. Data including feed intake, conversion ratio, and age at first laying, laying percentage, and egg quality parameters were collected. Statistical analysis was carried out using JMP. Chickens fed with EM in feed and drinking water had higher egg production percentage. There was a significant difference in egg laying percentage between the treated and control groups (P<0.001). Eggs from chickens given EM in feed and water were 6% heavier in weight than those from control birds. Lower feed daily intake (115.5 gram) and feed conversion rate (2.05) were achieved in chickens treated with EM in feed and water. Significant improvement on egg quality was revealed in chickens that received EM in feed and water. From this experiment, it can be concluded that the use of EM in feed and water improves egg production in layer chickens and therefore recommended for medium-scale poultry farms in Northern Ethiopia.